Gut microbiota in dysmenorrhea: causal evidence from Mendelian randomization and microbial-targeted intervention validation - Qin, Yajie; Ma, Rui; Zhang, Lili; Yang, Xiaotian; Zhou, Huifang; Wang, Yanping (Frontiers in Microbiology, 2026)
BackgroundDysmenorrhea is a prevalent gynecological disorder with multifactorial pathophysiology, including prostaglandin overproduction, inflammation, and pain sensitization. Emerging evidence suggests that gut microbiota may contribute to pain modulation, although causal relationships remain unclear.MethodsBidirectional two-sample Mendelian randomization (MR) was performed to investigate causal associations between dysmenorrhea and gut microbiota. Complementary in vivo validation was conducted in a primary dysmenorrhea (PDM) rat model treated with ibuprofen or the traditional Chinese medicine Wenjing Zhitong Decoction (WJZTD). The gut microbiota composition was analyzed using 16S rRNA sequencing, and correlations with pain-related parameters were assessed.ResultsForward MR analyses revealed that genetic liability to dysmenorrhea influenced the abundance of specific gut taxa, notably reducing Lachnospiraceae genera and increasing Erysipelotrichaceae, which was consistent with observed alterations in PDM rats. Reverse MR provided no robust evidence that gut microbiota causally affect dysmenorrhea. In the PDM model, both ibuprofen and WJZTD produced analgesic effects, but induced distinct microbial signatures: ibuprofen increased the presence of Staphylococcus, while WJZTD enriched the population of Bifidobacterium. Correlation analyses highlighted Blautia as a microbiota feature associated with reduced pain, suggesting that modulation of this genus may represent a potential therapeutic strategy.ConclusionThis study demonstrates that dysmenorrhea causally alters gut microbiota composition. The restoration of Blautia and Bifidobacterium by WJZTD is associated with pain alleviation, highlighting gut microbiota modulation as a potential strategy for dysmenorrhea management.